Carbon Footprints in the Nordics: Do dietary choices of Nordic households affect their consumption-based carbon footprints? - Húbert Óðinn Huntingdon-Williams 1995- (2023)
The Nordic nations are at the forefront of global climate issues due to their enormous focus on the supply and production of renewable energy. Despite that, the consumption-based carbon footprint (CBCF) of the people of the Nordic countries is so high that they are among the countries that emit the most in the world. Aim of the study is to examine the carbon footprint of the Nordic population based on different diets and meat consumption. The data on which the study is based are the results of an online survey that was conducted in the Nordic countries and included approx. 8000 participants. Emphasis is placed on how diet and socio-economic factors are analyzed concerning consumption-based carbon footprints, for example, diet, housing, vehicle use, public transport, leisure travel, goods and services, pets, and summer cottages. Bivariate and regression analysis was used in the GNU PSPP format. The results were as follows; Denmark has the highest carbon footprint in the Nordic countries. Whereas the average Dane has 8.4 tCO2-eq/cap. This was followed by Iceland and Finland (7.8 tCO2-eq/cap), Norway (7.2 tCO-eq/cap), and Sweden (6.4 tCO-eq/cap). For all diet groups, alternative diets had the lowest CBCF. An average Norwegian vegan emits the lowest 4.1 tCO2-eq/cap to an average vegan in Iceland and Denmark emitting 6.0 tCO2-eq/cap. The lowest vegetarian diet was an average Swede with 5.0 tCO2-eq/cap compared to an average Dane with of 6.8 tCO2-eq/cap. The lowest pescatarian was an average Swede with 5.6 tCO-eq/cap compared to an average Danish pescatarian with 7.6 tCO-eq/cap. Omnivore diet contributed the most to the CBCF. On average, a daily meat eater in Denmark has 9.1 tCO2-eq/cap, followed by Finland (8.4 tCO2-eq/cap), Iceland (8.2 tCO2-eq/cap), Norway (7.4 tCO2-eq/cap), and finally Sweden (6.8 tCO2-eq/cap). The results show that dietary choice was found to affect the overall footprint in Nordics. With domains of diet, goods and services, and vehicle use having the biggest impact on the Nordic CBCF. The ...